Heat capacity and thermodynamic functions of new nanostructured cuprate-manganite NdCa2CuMnO6 - Kasenova, Sh. B.; Kasenov, B. K.; Sagintaeva, Zh. I.; Bekturganov, N. S.; Ermaganbetov, K. T.; Kuanyshbekov, E. E.; Seisenova, A. A.; Smagulova, D. I. (Pleiades Publishing, 2014)
Heat capacities of nanostructured NdCa2CuMnO6 cuprate-manganite are measured by means of dynamic calorimetry on an IT-C-400 unit in the temperature interval of 298.15–673 K. It is established that a λ-shaped phase transition of the second kind is revealed at 348 K on the curve of the dependence C° p ∼ f(T) of NdCa2CuMnO6. Equations for the temperature dependence of the heat capacity of NdCa2CuMnO6 cuprate-manganite are derived from experimental data including the temperature of phase transition. Thermodynamic functions H°(T)-H°(298.15), S°(T), and Φ**(T) are calculated in the interval of 298.15–675 K.
Keywords: cuprate-manganite; heat capacity; thermodynamic functions